2019
DOI: 10.2474/trol.14.411
|View full text |Cite
|
Sign up to set email alerts
|

Friction Reduction of Palm Kernel Activated Carbon Polymer Composite by Lubricant Impregnation

Abstract: The purpose of this research is to propose a technique for friction reduction of palm kernel activated carbon (PKAC) polymer composite by palm oil, paraffin oil and water impregnations. A biocomposite sample formed by mixing epoxy and PKAC was made using the method of powder metallurgy. Before test of dry sliding, the sample was impregnated with palm oil, paraffin oil, and water for about 1-8 days. The test of dry sliding was then conducted at room temperature and by applying constant load, sliding distance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Various efforts have been made to eliminate or at least minimize friction losses such as introducing lubrication and its additives (Abdullah et al , 2016; Abdullah et al , 2014), development of new materials (Mahmud et al , 2019; Mahmud et al , 2017; Mat Tahir et al , 2016; Mat Tahir et al , 2015; Chua et al , 2014; Mustafa et al , 2014) and surface modifications (Amiruddin et al , 2019; Mohmad et al , 2017; Abdollah et al , 2013; Abdollah et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various efforts have been made to eliminate or at least minimize friction losses such as introducing lubrication and its additives (Abdullah et al , 2016; Abdullah et al , 2014), development of new materials (Mahmud et al , 2019; Mahmud et al , 2017; Mat Tahir et al , 2016; Mat Tahir et al , 2015; Chua et al , 2014; Mustafa et al , 2014) and surface modifications (Amiruddin et al , 2019; Mohmad et al , 2017; Abdollah et al , 2013; Abdollah et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Amiruddin et al (2019) attempt to reduce friction and wear by lubricant impregnated into the palm kernel-activated carbon epoxy composite for a certain period before a dry sliding test. They found that the composite porosity absorbs the lubricant and acts as a reservoir to reduce friction despite left to be dried for a specified period.…”
Section: Introductionmentioning
confidence: 99%